Sequential Organ Failure Assessment (SOFA) Score as a Predictor of Outcome in Patients Admitted in a Medical ICU (Medical Forum Monthly, 2024)
Objective: To assess the efficacy of Sequential Organ Failure Assessment score (SOFA) as a determinant of outcome in critically ill medical patients.Study Design: Prospective observational cohort study Place and Duration of Study: This study was conducted at Medical ICU of Civil Hospital Karachi from June 2014 to December 2014.Materials and Methods: The study was conducted on 152 patients admitted in the Medical ICU. The SOFA score was calculated on admission and thereafter daily until ICU discharge or death. The primary outcome measure was ICU mortality. The initial SOFA score, the SOFA scores at 48 and 72 hours, the mean and highest SOFA scores and the trend of SOFA score during the initial 48 hours were correlated with mortality.Results: The overall ICU mortality rate was 35.5 % (n=54). Patients with an initial SOFA score of ≤ 9 had a mortality rate of 28.9%, while patients with an initial SOFA score of ≥ 10 had a mortality rate of 88.2 %. The SOFA scores at 48 and 72 hours also showed significant association with mortality. The mortality rates of patients having a score of ≤9 at 48 and 72 hours were 25.6% and 20% respectively while the mortality rates of those with a score of ≥10 at 48 and 72 hours were 91.3% and 93.8% respectively. A sharp rise in mortality was seen when the Highest SOFA score during the entire ICU stay exceeded 7. Patients having a mean SOFA score of greater than 5 had a mortality rate of 66.7% regardless of length of stay. Univariate Logistic Regression Analysis revealed that the Highest SOFA score had closest correlation with mortality followed by Mean SOFA score, SOFA at 48hours, and SOFA at 72 hours. The biggest area under the receiver operating characteristic curve (AUROCC) was seen for the Highest SOFA score followed by SOFA at 72 hours, Mean SOFA score and SOFA at 48hours. Analysis of the changes in SOFA score during the first 48 hours depicted a mortality rate of 54.9% when the score increased, 27.6% when the score decreased and 23.3% when it did not change.Conclusion: The serial evaluation of SOFA score proved to be a convenient and efficient tool to predict mortality in the critically ill ICU patients.